ABSORBENT PENYARINGAN TERURUT DARI SEMIGRUP IMPLIKATIF - Tutut Irla Multi (Jurusan Matematika FMIPA Universitas Andalas Padang, 2015)
The simplest algebraic structure is called groupoid, where groupoid isnonempty set with a binary operation. The groupoid which is associative is called asemigroup. A negatively partially ordered semigroup is a set A with a partial orderingand a binary operation. Such A is called implicative if there is an additional binary operation.In this paper will be reviewed the notion of absorbent ordered lters in implicativesemigroups. Then it will be studied the relations among ordered lters, absorbent orderedlters, and positive implicative ordered lters.